Artistic conception in meticulous Chinese flowers and birds painting / Yao Libin, Liza Marziana Mohammad Noh and Haslinda Abd Razak - Libin, Yao; Mohammad Noh, Liza Marziana; Abd Razak, Haslinda (Faculty of Art and Design, 2024)
Chinese painting has its own unique form of artistic expression, which aims to convey the inner emotion and spirits of each one and other. with more and more people being fond of Chinese meticulous painting, their aesthetic views on it are also constantly improving, and they are increasingly emphasising on feeling the spirit of Chinese meticulous painting of flowers and birds through the expression of their own works. Chinese meticulous painting is an inheritance of Chinese excellent traditions, and the images displayed through the paintings can allow viewers to feel the true emotions of the creators. artistic conception is the soul of meticulous flowers and birds painting, the rich connotation of meticulous flowers and birds painting art in various periods, and also the source and core of creating it. In spite of this importance, there are deficiencies in the analysis of artistic conception in contemporary meticulous flowers and birds painting in the current literature. This study attempts to fill up the deficiencies by analysing the relevant content of artistic conception, focusing on the analysis artistic conception of Chinese meticulous flowers and birds painting.